The Insecticide Toxicity and Repelling Ability of Jeruk Purut (Citrus hystrix D.C) Leaf Extract on Maize Weevil (Sitophilus zeamais Motsch) - Alfia Wulansari; Nur Rochman; Setyono Setyono (JURNAL AGRONIDA, 2019)
Sitophilus zeamais Motsch. is a primary storage insect pest damaging maize grains. Control of S. zeamais can be done by applying biopesticide. This study was aimed at assessing the ability of Jeruk Purut leaf extract, as biopesticide, to kill and repel Sitophilus zeamais Motsch. The study was conducted at Entomology Laboratory, Seameo Biotrop in March to August 2018. A completely randomized design with three replicates in each rate of Jeruk Purut leaf extract was used. In preliminary pesticide toxicity experiment, five rates of Jeruk Purut leaf extract, namely 0%, 2%, 4%, 6%, and 8% were applied. In preliminary repelling ability experiment, five rates of Jeruk Purut leaf extract, namely 1%, 2%, 4%, 6%, and 8% were applied. In the main pesticide toxicity and repelling ability trial, five rates of Jeruk Purut leaf extract, namely 3%, 6%, 9%, 12%, and 15% were applied. Results showed that in 24 hour after treating (HAT) no significant effects were found. Significant effects of Jeruk Purut leaf extract as insecticide on S. zeamais were found in 48 and 72 HAT. The highest mortality rate (82.2%) of S. zeamais was found in 15% rate of Jeruk Purut leaf extract in 72 HAT. The application of Jeruk Purut leaf extract was not found to give significant effects on repelling S. zeamais in 24, 48, and 72 HAT as indicated in their sharply fluctuating repellent values. The highest repelling ability (95%) was found in the application of 9% Jeruk Purut leaf extract in 24 HAT. It was concluded that Jeruk Purut leaf extract was more potential as insecticide repellent for Sitophilus zeamais Motsch. Key words: biopesticide, repellent, insecticide, maize, primary storage insect pest